2017
DOI: 10.1007/s00394-017-1394-2
|View full text |Cite
|
Sign up to set email alerts
|

Daily supplementation with fresh pomegranate juice increases paraoxonase 1 expression and activity in mice fed a high-fat diet

Abstract: These results suggest that PJ protects against the effects of a high-fat diet in body weight, and cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 34 publications
5
38
0
2
Order By: Relevance
“…According to previous research, changes exerted by MP on APOA1 may occur for a number of reasons. For example, polyphenols from pomegranate juice increase the serum activity and hepatic mRNA expression of paraoxonase 1 (PON1), an enzyme that closely associates with HDL particles, which results in decreased serum lipids in mice that are fed diets rich in fat, cholesterol and sodium cholate . Cyanidin has been shown to promote RCT by increasing mRNA expression of ABCA1 and ABCG1 transporters in human aortic endothelial cells, and both transporters play important roles in preventing cholesterol overload by exporting it to HDL .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous research, changes exerted by MP on APOA1 may occur for a number of reasons. For example, polyphenols from pomegranate juice increase the serum activity and hepatic mRNA expression of paraoxonase 1 (PON1), an enzyme that closely associates with HDL particles, which results in decreased serum lipids in mice that are fed diets rich in fat, cholesterol and sodium cholate . Cyanidin has been shown to promote RCT by increasing mRNA expression of ABCA1 and ABCG1 transporters in human aortic endothelial cells, and both transporters play important roles in preventing cholesterol overload by exporting it to HDL .…”
Section: Resultsmentioning
confidence: 99%
“…For example, polyphenols from pomegranate juice increase the serum activity and hepatic mRNA expression of paraoxonase 1 (PON1), an enzyme that closely associates with HDL particles, which results in decreased serum lipids in mice that are fed diets rich in fat, cholesterol and sodium cholate. 55 Cyanidin has been shown to promote RCT by increasing mRNA expression of ABCA1 and ABCG1 transporters in human aortic endothelial cells, and both transporters play important roles in preventing cholesterol overload by exporting it to HDL. 56 An anthocyanin-rich black elderberry extract has been shown to improve HDL function and decrease aortic cholesterol in hyperlipidemic mice by modulating the hepatic mRNA expression of various HDL-related genes, without significant changes to the serum HDL or APOA1 concentration.…”
Section: Gene Expressionmentioning
confidence: 99%
“…36,37 Similarly, the lack of PJ effect on the total and LDL cholesterol in our study may be partly due to relatively normal levels of these lipids in the participants as other studies on diabetes patients with elevated blood lipids showed promising results. 38,39 The lipid-lowering and anti-atherogenic properties of pomegranate may be attributed to a number of mechanisms such as regulating the expression of the genes involved in lipogenesis and fatty acid oxidation in the liver 40 ; increasing the expression and activity of paraoxonase-1; the antioxidant enzyme in HDL particles which prevents LDL oxidation 41 ; and suppression of oxidized LDL degradation and of cholesterol synthesis in macrophages. 42 Along the same lines as our results, investigations have reported pomegranate antioxidant potential as evidenced by decreased MDA 38,39,43,44 and increased serum total TAC.…”
Section: Discussionmentioning
confidence: 99%
“…PON1 is synthesized in the liver and transported in plasma in association with HDL. The decrease in the PON1 activity may lead to higher levels of cholesterol (Estrada-Luna et al, 2018). Other associated paraoxonase are PON2 and PON3.…”
Section: Introductionmentioning
confidence: 99%